Studi Bibliometrik Implementasi Teknik Machine learning dalam Bidang Customer Relationship Management - Khaerul Anam (Ikatan Ahli Informatika Indonesia, 2024)
Application of machine learning techniques in Customer Relationship Management has proven to have significant potential in enhancing the efficiency and effectiveness of managing customer interactions. This study aims to conduct a comprehensive bibliometric analysis regarding the application of machine learning techniques in CRM. Through this analysis, we seek to identify recent research trends, gaps, and future research opportunities. This study utilizes data from various prestigious international scientific journals indexed by Scopus to explore the application of machine learning techniques for churn prediction models. The method employed in this research is bibliometric analysis on machine learning techniques in the field of CRM. This study reveals a significant trend in the application of machine learning techniques in Customer Relationship Management. The results indicate that the use of machine learning in CRM has increased, particularly since 2021, reflecting a high interest and the relevance of this technology in enhancing the efficiency and effectiveness of CRM. The analysis also shows that the discipline of computer science dominates this research, followed by engineering, business and management, and mathematics. The contribution of this research to existing knowledge is providing a deeper understanding of current research trends and identifying gaps and future research opportunities.